ORAL ANTICOAGULANT PRESCRIBING IN A HYPERACUTE STROKE UNIT. Issue 11 (14th October 2015) - Samani, Amit; Kayani, Mahaz; Asokanathan, Asaipillai
Abstract : Background: Non-vitamin K antagonist oral anticoagulants provide a valuable alternative option to warfarin for thromboprophylaxis for non-valvular atrial fibrillation. NICE has recently released a national consensus statement which will guide local protocol/guideline development. Currently, their use is often governed by physician preference combined with patient factors. We explored the pattern of prescribing in the pre-guideline era. Method: Retrospective analysis of admissions from June–October 2014. Student T-test and Fischer's exact test with Bonferroni corrections were used to compare demographics between groups. A creatinine clearance of <60 umol/L defined renal impairment. Results: 61 patients, 37 female, mean age 80.8 years were audited. 35 were prescribed rivoroxaban 20 mg, 7 rivoroxaban 15 mg, 11 apixaban 5 mg and 8 apixaban 2.5 mg. None were prescribed dabigatran. Age, CHADS2 and HAS-BLED scores did not show statistically significant variability between subgroups. Renal impairment was signficantly commoner in the apixaban 2.5 mg group compared to the 5mg group (p<0.001) and the rivoroxaban 15mg compared to the 20mg group (P<0.01). There was no difference between the rivoroxaban and apixaban groups. Conclusion: Currently, renal impairment is the main determinant for thromboprophylaxis choice. Local guidelines have been created with physician education underway and re-audit planned in 3 months. The authors will present the full data.